Volume 5: 37th Design Automation Conference, Parts a and B 2011
DOI: 10.1115/detc2011-48000
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Honeycomb Cellular Meso-Structures for High Speed Impact Energy Absorption

Abstract: This paper presents the energy absorption properties of hexagonal honeycomb structures of varying cellular geometries to high speed in-plane impact. While the impact responses in terms of energy absorption and densification strains have been extensively researched and reported, a gap is identified in the generalization of honeycombs with controlled and varying geometric parameters. This paper attempts to address this gap through a series of finite element (FE) simulations where cell angle and angled wall thick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…Impact and indentation investigations have previously been reported on auxetic polymeric and metallic foams, sandwich panels comprising kevlar fabric‐epoxy honeycomb core and fibre‐reinforced polymer skins , carbon fibre‐reinforced epoxy laminates , polymers containing auxetic chopped fibres and microporous polymers . A number of theoretical treatments are also present in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…Impact and indentation investigations have previously been reported on auxetic polymeric and metallic foams, sandwich panels comprising kevlar fabric‐epoxy honeycomb core and fibre‐reinforced polymer skins , carbon fibre‐reinforced epoxy laminates , polymers containing auxetic chopped fibres and microporous polymers . A number of theoretical treatments are also present in the literature .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many examples of multiobjective optimization problems can be found, which further restricts the choice of optimizer if all objectives are to be considered (Namvar and Vosoughi, 2020;Paz et al, 2014Paz et al, , 2015Wang et al, 2017;Yin et al, 2011). The most common choices for an optimizer found for these problems have been surrogate optimization (Paz et al, 2014(Paz et al, , 2015Sun et al, 2010), and evolutionary and heuristic optimization techniques (Huang et al, 2021;Namvar and Vosoughi, 2020;Schultz et al, 2011;Wang et al, 2017;Yin et al, 2011). Surrogate optimizations rely on fitting easily differentiable functions to computed designs in the objective space.…”
Section: Introductionmentioning
confidence: 99%
“…Ingrola et al compared and analyzed the in-plane axial compressive performance between conventional honeycomb sandwich panels and negative Poisson's ratio inner hexagonal honeycomb sandwich panels by using 3D printing technology [24]. Schultz et al studied the influence of cellular cell geometric parameters on the energy absorption of honeycomb sandwich structures under high-speed in-plane impact load by statistical sensitivity analyses, and the results showed that the energy absorption rate was the highest when the cellular configuration presented a negative Poisson's ratio [25]. Yu et al proposed the hybrid CNTRC/metal laminated plates with an out-of-plane negative Poisson's ratio (NPR), and studied its nonlinear vibration [26].…”
Section: Introductionmentioning
confidence: 99%